Buyer’ Black Box Model Change in COVID-19 Pandemic - Daniel Hermawan (Sekolah Tinggi Manajemen IPMI, 2021)
The COVID-19 pandemic has changed the structure of human life globally, starting from the social, economic, political, health aspects, and so on. This study attempts to map the impact of changes in Generation Z consumer behavior in the period before and after the COVID-19 pandemic took place with the black box model in 3 stages, namely stimuli, transformers, and responses. The study was conducted on 186 undergraduate students with an age range of 17-24 years in measuring changes in 3 aspects, namely consumption patterns, entertainment, and basic necessities. The research model uses mixed methods with concurrent models, through the type of concurrent triangulation strategy. The results showed that there was a significant change in consumption and entertainment patterns in terms of the selection of purchasing methods and processes. Surprisingly, the pattern of shopping for basic necessities tends to not experience significant changes and contrasts with the media coverage of panic buying.